Is borderline personality disorder the cause of chronic headache? - Martins, Hugo André de Lima (Avanços em Medicina, 2025)
Patients with chronic headache are challenging for the clinician and often refractory to pharmacological treatment. Personality disorders affect up to 10% of the population, and borderline personality disorder is the most prevalent. It is characterized by a high degree of impulsivity, emotional instability, interpersonal relationship problems, fragile self-esteem, and pain distortion, which may often be the cause but not a consequence of chronic Headache.